Dabigatran-related platelet thrombin response during triple anti-thrombotic therapy: A matter of time?. Issue 149 (January 2017) - Witkowski, Marco; Steffens, Daniel; Hassanein, Adel; Witkowski, Mario; Kränkel, Nicolle; Doerner, Andrea; Friebel, Julian; Landmesser, Ulf; Rauch, Ursula
Highlights: If and when dabigatran alters platelet aggregation remains controversial. Platelet reactivity was analyzed after coronary stenting in patients on OAC. Dabigatran enhanced the TRAP-induced platelet reactivity after the first dose. Platelet thrombin exposure due to dabigatran dose missing may trigger thrombosis. Co-medication with amiodarone does not alter platelet reactivity.